Investigating shared and distinct mechanisms in semantic and syntactic enrichment: a priming study - Ito, A; Husband, EM (Taylor and Francis, 2022)
Aspectual verbs (e.g. begin) and intensional verbs (e.g. want) can both take entity-denoting NPs as a complement (begin/want the book) and acquire an implicit meaning (e.g. reading). Linguistic theory posits that such enriched implicit meanings can be acquired either by semantic enrichment with aspectual verbs or by syntactic enrichment with intensional verbs. To investigate whether semantic and syntactic enrichment share enrichment operations, we conducted a structural priming study. Experiment 1 repeated the verb on prime and target trials and found evidence for enrichment priming for both verb types. Experiment 2 crossed the verb type and found no evidence for priming. These results suggest that enrichment operations are distinct for aspectual and intensional verbs. However, Experiment 3 repeated Experiment 1 without lexical boost and found no enrichment priming within the verb type. Thus, producing an enriched structure may not robustly activate enrichment structures, leaving open questions concerning shared mechanisms.